Subsurface geology of Eniwetok Atoll - Schlanger, Seymour O. (Seymour Oscar), 1927-1990 (Bikini and nearby atolls, Marshall Islands., 1963)
"A study of limestone and dolomite recovered during deep drilling on Eniwetok."